Minería y conflictos sociales en la parroquia Telimbela, cantón Chimbo, provincia Bolívar, 2021-2022 - Cisneros Jimenez, Lizbeth Tatyana (2023)
The research work presented below addresses the issue of social conflicts due to mining and how these arise in the territory of Telimbela, they are analyzed based on the information collected through the mixed method, carrying out a bibliographic review of mining, the theory of conflict and the theory of resource mobilization to later carry out the corresponding surveys, which were applied to 344 people who were the population sample of the sector. Within the surveys, possible factors that generate the conflicts are analyzed and evidence if there was a socialization; and two interviews, one with the representative of the parish and one with the company. The objective of this research was to study the social conflicts due to the mining process, in the Telimbela parish, Chimbo canton, Bolívar province, through interviews, surveys, to find out the causes and possible future confrontations.Starting with the hypothesis that the mining conflict in Telimbela arises from the distrust of the population regarding the impact of mining in the sector, the factors causing the social mining conflict within the Telimbela parish and the effectiveness of the mechanisms used to the socialization of the same in the territory, it is concluded that, if there was socialization about the mining project by the Yankuang mining company, however, the appropriate mechanisms were not applied to reach the entire corresponding territory, indicating that there were flaws in the management of the information